Shadow bank runs - David Andolfatto; Ed Nosal (Federal Reserve Bank of Atlanta, 2020)
Short-term debt is commonly used to fund illiquid assets. A conventional view asserts that such arrangements are run-prone in part because redemptions must be processed on a first-come, first-served basis. This sequential service protocol, however, appears absent in the wholesale banking sector-and yet, shadow banks appear vulnerable to runs. We explain how banking arrangements that fund fixed-cost operations using short-term debt can be run-prone even in the absence of sequential service. Interventions designed to eliminate run risk may or may not improve depositor welfare. We describe how optimal policies vary under different conditions and compare these to recent policy interventions by the Securities and Exchange Commission and the Federal Reserve. We conclude that the conventional view concerning the societal benefits of liquidity transformation and its recommendations for prudential policy extend far beyond their application to depository institutions.
Keywords: G01; G21; G28; 330; shadow banks; bank runs; short-term debt